Technology 4.0 with 0.0 costs: fuzzy model of lettuce productivity with magnetized water - Matulovic, Mariana [UNESP]; Putti, Fernando Ferrari [UNESP]; Cremasco, Camila Pires [UNESP]; Almeida Gabriel Filho, Luis Roberto [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2021)
In agriculture with 4.0 technologies, developing a decision model with a 0.0 cost is attractive to small farmers. In water management, if this approach could be used to promote sustainability and optimization, it could become a pathway to reach the sustainable development goal in 2030. The core of this work is the development of a 4.0 mathematical model (based on fuzzy concepts) to verify the benefits of the production of lettuce irrigated with magnetically treated water at different replacement rates. This approach is achieved using computational 4.0 software and manual methods. The aim of mathematical modeling is to understand or explain a natural phenomenon associated with a given area of knowledge, and fuzzy-rule-based systems have been widely used in different types of in-depth research.
Keywords: fuzzy model; agriculture 4.0; elementary math; horticulture; magnetized water